Verruciform xanthoma in recessive dystrophic epidermolysis bullosa and keratitis‐ichthyosis‐deafness syndrome: Report of two cases and a review of the literature. Issue 1 (11th November 2019) - Evan‐Browning, Eric; Rork, Jillian; O'Donnell, Patrick; Elaba, Zendee; Deng, April; Wiss, Karen
Abstract: Verruciform xanthoma is a benign, wart‐like lesion that can clinically mimic squamous cell carcinoma. We describe two teenage patients with severe genodermatoses, recessive dystrophic epidermolysis bullosa (RDEB), and keratitis‐ichthyosis‐deafness (KID) syndrome, respectively, each found to have plaques suspicious for malignancy, later demonstrated on histopathologic examination to be verruciform xanthoma. We discuss the connection between these severe genodermatoses and the suspected pathophysiology of verruciform xanthoma. In addition, we highlight the importance of recognizing verruciform xanthoma as a clinical mimicker of squamous cell carcinoma, for which patients with RDEB and KID syndrome are at increased risk.